The Realizations of Code-Switching in Kompas Newspapers : A Study in Political and Law Articles - Ambarita, Esron; Br. Gultom, Grace Gabriela (Journal of Applied Linguistics, 2024)
This study aimed to investigate the realizations of code-switching in KOMPAS, a leading national newspaper in Indonesia with the highest editorial quality from an Indonesian perspective. The study is restricted to political and law articles by doing an in-depth descriptive analysis to reveal the goals. This study used a qualitative descriptive method dealing with a quantifiable mode. The results show that code-switching in quoted statements in political and law articles in KOMPAS newspapers was realized in (1) English words with meanings, (2) English words without meanings, (3) combination of Indonesian prefixes and English words, (4) combination of English words and Indonesian suffixes, (5) English phrases, (6) repeated English interjections, (7) English sentences, and (8) combination of English words and English sentences in one utterance. Keywords: The realizations of code-switching; KOMPAS newspapers; Political and  law articles